Analisis Gaya Bahasa Dan Makna Dalam Lirik Lagu “RAYUAN PEREMPUAN GILA” Karya Nadin Amizah - Muthia Azahra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research contains a discussion of the use of language styles in the lyrics of the song by Nadin Amizah with the title